Hybridity in Ben Okri’s "Abiku" Trilogy - Barhoun, Brahim (Estudios Ingleses de la Universidad Complutense, 2013)
In its narrative style as well as in its cultural environment, magical realism provides the optimal literary field to respond to the cultural issues and conditions that traverse contemporary postcolonial society. For example, the codification in the magical-realist narrative of both colonial and postcolonial discourses, involved in a dialectical struggle, reflects many of the problematic relations existing between colonizer and colonized in postcolonial culture. This leads to the investigation of hybridity as an important trope in the ongoing process of literary and cultural decolonization. This article explores the function of hybridity in three novels by Ben Okri, showing how, through the destabilization of such spaces as the real and the imaginary, the new and the old, and the self and the other, a third space emerges where irreconcilable perspectives and contradictory properties coexist, although problematically. In this sense, the fictional space, time and characters displace polar oppositions and make it difficult to conceive of any version of reality as having a greater claim to absolute truth or unique referentiality. Consequently, and in theoretical and political terms, what magical realism tries to do here is replacing the dominant culture and its version of truth by a new mode of perception that opens up various levels of thought and accepts the possibility of many truths to be considered simultaneously and not hierarchically.